Electron pump-shuttle cathode enables coupled directed-electron flows for resource-oriented treatment of radioactive wastewater - Xijun Fu; Shuai Gao; Haodong Ji; Yanbiao Liu; Sujie Yang; Binsheng He; Ping Cao; Qingyan Zhang; Le Li; Yifeng Hu; Qingyi Zeng (Water Research, 2026)

Deep neural network-based prediction of sauce-flavor Baijiu fermentation process and regulation of flavor compound synthesis - Shiyuan Ma; Wei Cheng; Zhongfu Duan; Dan Huang; Ping Huang; Qiuxia Li; Siyuan Zeng; Rongqing Zhou; Yadong Zhang; Jiao Niu; Chongde Wu; Yi Shen (Bioresource Technology, 2026)

Control of Listeria monocytogenes in fresh-cut chili peppers by bacteriocin paracin wx7-1: Activity, mechanism, and preservative efficacy - Yushu Bian; Jinling Lin; Liuyang Li; Ping Zeng; Honghai Li; Lanhua Yi (Physiological and Molecular Plant Pathology, 2026)

Delta dynamics: Insights from high-density OSL chronology in the Han River Delta, Northern South China Sea - Ping Lai; Gui Long; Tiantian Huang; Guanjun Xu; Zibin Fang; Ziyuan Wu; Yuexin Liu; Penghui Lin; Xiwen Nong; Xiaojian Zeng; Hongwei Li; Zhongping Lai (Geomorphology, 2026)

Molecular-level analysis of atmospheric particulate organic compounds using HPLC-Orbitrap MS/MS: effects of solvents - Shan Xu; Minghui Lu; Ping Zeng; Meng Chang; Haoqian Wang; Xuehui He; Baode Xue; Xinyu Ji; Kuai Yu; Jingkun Jiang; Hairong Cheng; Xiaoxiao Li (ENGINEERING Environment, 2026)

Isolation and pathogenicity of Actinobacillus pleuropneumoniae Serovar 19 in pigs - Bo Hong; Guangyuan Yi; XvDong Lin; YingXuan Ye; XiaoLi Liu; Ahmed H. Ghonaim; Yang Zeng; Shuo Zhang; Ping Bai; Wentao Li; Xuexiang Yu; Qigai He (Veterinary Microbiology, 2026)

CvbZIP81 contributes to selenium accumulation by regulating sulfate transports in Cardamine violifolia - Luxin Feng; Jiarui Zheng; Sirui Zeng; Ge Li; Sisi Wang; Ping Yun; Zexiong Chen; Renhua Huang; Qiangwen Chen; Sergey Shabala; Feng Xu (Plant Science, 2026)

Tracking sedimentation process under progressive mangrove propagation in low-energy bays - Weiming Li; Zhijun Dai; Xuefei Mei; Jiejun Luo; Wenjun Zeng; Ping Zhang; Ran Chen; Jinping Cheng (Marine Geology, 2026)

Reactive oxygen species–mediated enhancement of cadmium phytoextraction in ramie (Boehmeria nivea L) by pyrite: Linking rhizosphere chemistry to plant metabolism - Tangshan Wu; Xiaofei Tan; Ping Chen; Chuang Li; Gaobin Chen; Zhenhong Huang; Genying Zeng; Yaqian Yang; Meijuan Zhang (Journal of Environmental Chemical Engineering, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Aging and photodegradation of polycyclic aromatic compounds (PACs) emitted from biomass burning under sunlight and ultraviolet radiation - Ya-Jing Li; Zhen-Shan Huang; Yu-Ping Chen; Zhi-Hui Su; Yi-Huan Chen; Yuan Zeng; Yu-Qi Huang; Yu-Feng Guan; She-Jun Chen (Atmospheric Environment, 2026)

Inside-out conversion of open pores into closed nanopores enables high-plateau hard carbon anodes for sodium-ion batteries - Zhuo Xiong; Rui Li; Ping Liu; Shuang Lin; Chaoshu Zhao; Wenyuan Fu; Jiale Shen; Lili Xiao; Xuedan Chen; Jianping Long; Xianguang Zeng; Anjun Hu; et al. (Chemical Engineering Journal, 2026)

Design and fabrication of structured adsorbents with enhanced mass transfer for direct air CO2 capture - Yifan Zhang; Bing Du; Kaijie Xuan; Jie Wu; Yongfa Li; Longchun Zhong; Ali Nabeeh Shakhs; George P. Lithoxoos; Rashid M. Othman; Faiz Almansour; Jiawei Wang; Xi Zeng; et al. (Chemical Engineering Journal, 2026)

A peroxisomal metabolic route from benzoyl-CoA to benzyl alcohol for phenylalanine-derived salicylic acid biosynthesis in rice - Yukang Wang; Shuyan Song; Wenxuan Zhang; Qianwen Deng; Yang Lai; Zhixue Huo; Shanshan Li; Qi Zhang; Yuchen Ping; Jiarong Chen; Zeng Tao; Yanlei Feng; et al. (Molecular Plant, 2026)

Unraveling the impact of food processing technologies on postbiotic bioactivity, food matrix interactions, and human health outcomes - Junxin Zhao; Mengfei Duan; Ruiying Xu; Yumeng Cheng; Jinheng Li; Deguo Wang; Xianghui Yan; Ping Yu; Zheling Zeng; Yunzhi Lin; Yoshimitsu Masuda; Ken-ichi Honjoh; et al. (Food Bioscience, 2026)

Benzophenone-2 disrupts craniofacial cartilage development via esr2a-Dependent inhibition of endothelin signaling in zebrafish larvae - Zhuoyi Xie; Keying Li; Xiaomai Zhou; Qiuchen Wu; Xiangrong Zhou; Ping Zeng; Jing Li; Qiao Niu; Zhipeng Qi; Xinying Zhao; Weiyi Song (Environmental Research, 2026)

Unraveling the critical role of ClO• in the degradation of emerging organic contaminants by far-UVC/chlorine: Radical contribution assessment and influence of water matrix - Ping Li; Ge Zeng; Wenjun Zhang; Qiuling Lu; Haonan Lu; Kai Wang; Jun Ma; Yan Zhang; Tao Yang (Chemical Engineering Journal, 2026)

Reliability-adaptive graph-cut phase unwrapping for InSAR geohazard deformation monitoring - Huadong Hu; Ping Zhang; Zhen Li; Jiangyuan Zeng; Haiwei Qiao; Yanan Bai; Siqing Xu; Hui Yuan (International Journal of Remote Sensing, 2026)

Taxonomy of Neostagonosporella on Chimonobambusa with descriptions of two new taxa - Xiu-Lan Xu; Yu Deng; Li-Ping Gao; Qian-Ying Huang; Wei Liu; Li Zhuang; Fei Chen; Qian-Gang Xiao; Zhen Zeng; Feng Liu; Qi-Rong Sun; Ying-Gao Liu; et al. (Mycological Progress, 2026)

Structural and rheological modulation of low-oil emulsions by deamidated pea protein–gum arabic coacervates for reduced-fat applications - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Chemistry, 2026)

Paleoclimatic evolution of the northeastern Tibetan Plateau margin during the Late Oligocene-Early Miocene: Evidence from Ostracod shell trace elements - Wei Chen; Jinlong Ma; Xiaofeng Wang; Xuan Li; Liang Zeng; Xiaoqing Jiang; Ping Yang; Houyong Luo; Ke Yin (Journal of Mountain Science, 2026)

Magnetically recoverable N-doped graphene/ZnFe-LDO composite for synergistic adsorption-photocatalytic removal of tetracycline in water - Le You; Tianqi Wang; Boya Zeng; Wu Zhang; Yuqing Huang; Zhanli Chen; Ping Zhang; Yujie Li; Bo Zeng (Applied Clay Science, 2026)

Oral co-exposure to Clostridioides difficile toxin A and ovalbumin disrupts intestinal homeostasis and predisposes to food allergy in mice - Xiaoqian Xu; Xiang Zeng; Youdou Cheng; Ping Yang; Jinyan Gao; Xuanyi Meng; Yong Wu; Xin Li; Ping Tong; Hongbing Chen (Toxicon, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

In vitro simulated digestion of Ganoderma lucidum proteoglycan and its effects on gut microbiota in type 2 diabetic rats - Qianqian Zhang; Xinru Zheng; Jieying Chen; Ying Zhang; Jiaqi Li; Yingxin Wang; Yanna Pan; Fanzhen Yu; Zeng Zhang; Hongjie Yang; Yanming He; Ping Zhou (Food Bioscience, 2026)

The aging eye: navigating molecular mechanisms and innovative interventions - Yumeng Lin; Zhongyu Han; Yunfeng Zhang; Ruimin Yuan; Mingyu Huang; Yating Liu; Jun Wang; Chen Xu; Luze Liu; Ping Yu; Qingsong Yang; Liuzhi Zeng; et al. (Biogerontology, 2026)

Characterization and source apportionment of halogenated organic pollutants in sediments from the Daya Bay, South China Sea - Ren-Jie Shang; Jian-Fang Hu; Ming-Yang Liu; Yao Xiao; Yi-Ting Zeng; Li-Tian Huang; Ping-An Peng (Marine Pollution Bulletin, 2026)

Reversible dormancy via gradient cooling ensures high survival and muscle quality through coordinated metabolic suppression and recovery in Litopenaeus vannamei - Yueqin Li; Ping Zhang; Ziyi Yin; Yuwei Zhang; Qiwei Du; Zhen Wu; Xiaoqun Zeng; Daodong Pan (Food Bioscience, 2026)

Next-generation chitosan biodegradable films reinforced with bioactive acid-DES: A sustainable solution for improved mechanical, antibacterial, and anti-browning properties - Dehong Lu; Huimin Yao; Nouman Ali Shah; Sajid Ali; Li-Yan Zeng; Ping Shi; Yuan-Sen Liu; Ziru Dai; Hafiz Umer Javed (Carbohydrate Polymers, 2026)

Eocene topography differentiation between the western and eastern North China Craton: Insights from multi-method chronometry in the northern Taihangshan Mountains - Li-Xia Feng; Ping-Ping Li; Zeng-Zhen Wang; Rong Ren; Lin Wu; Bo Zheng; Bo Liu; Jian-Qing Ji; Bao-Fu Han (Tectonophysics, 2026)

Photosensitive COFs-carboxylated nanocellulose membrane enables high-efficiency uranium extraction via synergistic coordination complexation and photocatalytic reduction - Shuaishuai Guo; Zhenlong Zeng; Dongyang Xu; Dingquan Li; Ping Cao; Jie Sun; Shiqin Zhang; Cheng Wang; Guowen Peng; Qingyi Zeng (Journal of Hazardous Materials, 2026)

Distribution pattern and development of typical antibiotic resistance genes in the continuous-flow aerobic granular sludge-membrane bioreactor system - Yongsheng Jiang; Yu Zeng; Lei Shang; Dehong Bai; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Journal of Environmental Chemical Engineering, 2026)

Mechanistic insights into high-pressure-induced structural and thermal changes of wheat starch in flour and dough systems - Yung-Jia Chan; Ping-Hsiu Huang; Xiao-Song Huang; Wen-Chien Lu; Zeng-Chin Liang; Po-Hsien Li (Food Hydrocolloids, 2026)

Electrochemical remediation technologies for persistent organic pollutants in soil and water - Ping Zhang; Qin Zeng; Longchun Yan; Hongyu Xiao; Zhihui Yang; Yuchun Li (Environmental Research, 2026)

Andrographolide Alleviates Inflammation in Chronic Obstructive Pulmonary Disease by Inhibiting Alveolar Macrophage Pyroptosis Through the JNK/NLRP3 Pathway - Tingting Zhang; Xiaofeng Li; Zhe Wang; Xin Li; Ping Huang; Xiaoli Zeng; Xiaoju Liu (Cell Biochemistry and Biophysics, 2026)

Sustainable postharvest management practices for kiwifruit: Principles, approaches, and future directions - Qinhong Liao; Xiaojiao Li; Shixian Zeng; Wenxuan Chen; Ping Huang; Zihao Wang; Chi Yan; Qiqiang Wu; Qiuhong Niu; Yong Wang; Zhenshuo Wang (Postharvest Biology and Technology, 2026)

Posttranslational regulation of TOR kinase activity controls resource allocation between plant growth and immunity in Arabidopsis - Jianwei Li; Ran Wang; Chenying Li; Xijie Guo; Qinghong Li; Zhixuan Wu; Shanshan Zeng; Fan Qi; Yuchen Wang; Zhiyi Jia; Weiwei Yu; Zeming Huang; et al. (Molecular Plant, 2026)

Impact of boiling-drying regimes on milling properties, digestion characteristics, and multi-scale starch structure of parboiled rice - Yi Wang; Jiarui Zeng; Yuying He; Guang Liu; Pengfei Zhou; Ping Li; Zhihao Zhao; Mingwei Zhang; Cuiping Yi; Yuanyuan Deng (Food Research International, 2026)

Enhancement of protein gelation and nutritional properties in pea protein gels through enzymatic deamidation - Lijuan Luo; Ping Li; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Pengfei Zhou; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang (Food Hydrocolloids, 2026)

Microscopic mechanisms of dissolved organic matter sequestration and transformation at the mineral-water interfaces during the formation and transformation of Fe Mn (hydr)oxides - Kai Cui; Libin Wu; Zihao Wu; Yue Yang; Shiwen Hu; Xiaoyuan Zhang; Zilong Zeng; Ping Chen; Li Wang; Zecong Ding; Hao Yi (Chemical Engineering Journal, 2026)

Plastome structure, repetitive sequences, and phylogeny of Orophea hainanensis (Annonaceae) - Jingyao Ping; Dong Tan; Aimin Li; Yangying Gan; Xianhai Zeng (Genetic Resources and Crop Evolution, 2026)

Tumor microenvironment-driven ST6Gal-Ⅰ activation promotes aggressiveness in gastric signet-ring cell carcinoma via ITGβ1/FAK/Paxillin signaling - Shuhong Zeng; Lihuiping Tao; Yingjie Gao; Xueying Yang; Zhiyu Li; Ziwen Li; Luhua Wu; Zhengchen Ping; Qian Zhao; Jiayi Gu; Liu Li; Dongdong Sun; et al. (Tissue and Cell, 2026)

Aloperine mitigates cigarette smoke-induced inflammation and pyroptosis by inhibiting the BRD4/NLRP3/GSDMD pathway in chronic obstructive pulmonary disease - Xiaofeng Li; Zhe Wang; Tingting Zhang; Xiaoli Zeng; Xin Li; Kai Liu; Ping Huang; Xiaoju Liu (Toxicology and Applied Pharmacology, 2026)

Global, regional, and national burden of hepatocellular carcinoma and contribution of nine modifiable risk factors across 185 countries/territories in 2022 - Ping Li; Zhan Ding; Yuqi Feng; Xiangyu Ren; Yongyue Wei; Changfa Xia; Yitao Yang; Quanbo Yang; Zhe Wang; Xuehong Zhang; L.G. van der Geest; Herbert Yu; et al. (Science Bulletin, 2026)

Behavioral toxicity of tralopyril in Oryzias melastigma: Integrated consequences of multi-organ damage and thyroid hormone dysregulation - Bin Liu; Tengzhou Li; Bianhao Zeng; Haiyang Yin; Le Sun; Ling Liu; Ping Li; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Brachymonas moutaii sp. nov., a floc-forming bacterium isolated from a distillery wastewater treatment plant - Yaqi Liu; Hui Wang; Ansi Jiang; Junmei Wu; Bi Chen; Yong Zhang; Siliang Yuan; Yan Huang; Haiyan Zeng; Xin Wang; Dian Jiao; Wei Li; et al. (Antonie van Leeuwenhoek, 2026)

Design, synthesis and cytotoxic activity of sulfonylated derivatives of camptothecin - Xiong-Fei Luo; Zhi-Jun Zhang; Zi-Long Song; Zhi-Ping Wang; Jia-Xuan Yan; Xiao-Fei Liu; Li-Zeng Peng; Cheng-Jie Yang; Ying-Qian Liu (Natural Product Research, 2026)

The effect of enrofloxacin exposure on energy metabolism and the ARGs transmission in grass carp: Potential contribution of microbiota-gut-liver axis - Ping Li; Bianhao Zeng; Xuqian Cao; Bin Liu; Ling Liu; Yi Chai; Zhi-Hua Li (Aquaculture, 2026)

Performance, metabolism, and resistance of an SMX-stressed continuous-flow AGS-MBR system: Microscopic mechanism of macroscopic instability phenomena - Yu Zeng; Haowei Gao; Huiya Huang; Wenqiang Xiong; Liying Bin; Bingda Liao; Weirui Chen; Xinyi Chen; Shanglong Wen; Ping Li; Shaosong Huang; Bing Tang (Water Research, 2026)

A novel potential toxic target of PBDEs in cetaceans: Impaired wound healing demonstrated in Indo-Pacific finless porpoise fibroblasts - Yajing Sun; Chengzhang Li; Ying Zeng; Imran Rashid Rajput; Jiashen Tian; Yuqi Wu; Juntao Ye; Ziyan Wang; Qinghong Liao; Jiezhang Mo; Zonghang Zhang; Jianqing Lin; et al. (Journal of Hazardous Materials, 2026)

The gut as a reservoir of drug-resistant pathogens: Mechanisms of ENR-driven horizontal gene transfer in aquaculture - Bian-Hao Zeng; Ping Li; Hao-Ran Zhang; Bang-Hua Xia; Bin Liu; Ling-Ming Kong; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2026)

Corrigendum to “Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment” [Chem. Eng. J. Volume 515, 1 July 2025, 163509/CEJ-D-25-01484R1] - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2026)

Oral Administrations of Short-Chain Fatty Acids or Probiotics Extend the Survival Times and Mitigate the Neuropathological Damages in the Scrapie-Infected Hamsters - Yuan Wang; Dong-Lin Liang; Run-Dong Cao; Ruhan A.; Jia-Feng Zeng; Bing Xu; Ju-Zheng Li; Wei-Wei Zhang; Li-Ping Gao; Kang Xiao; Xiao-Ping Dong; Qi Shi (Molecular Neurobiology, 2026)

Flow characteristics and velocity prediction considering changes in frontal area of submerged flexible vegetation - Ze-Kun Meng; Ping Wang; Yuyan Liu; Li Zeng (Journal of Hydrology, 2025)

“Pit-type Defects” strategy to improve the thermal stability of silver-based catalysts and copper-based catalysts - Yatong Pang; Chunxue Wang; Ziruo Zeng; Kai Li; Yixing Ma; Yuan Li; Fei Wang; Ping Ning (Journal of Environmental Sciences, 2025)

Fabrication of oil-in-natural deep eutectic solvents Pickering interfacial catalysis: Boosting a sustainable platform for enzymatic esterification of high-acid oil - Liyan Pan; Weiqi Liu; Yuanyuan Deng; Guang Liu; Yan Zhang; Xiaojun Tang; Ping Li; Zhihao Zhao; Jiarui Zeng; Mingwei Zhang; Pengfei Zhou (Food Chemistry, 2025)

Development of eco-friendly chitosan films enhanced with bioactive citric acid-based deep eutectic agents for sustainable food packaging and fish preservation - Ping Shi; Xin Wang; Sajid Ali; Li-Yan Zeng; Xinhui Xian; Jinling Huang; Shengyun Qin; Yuansen Liu; Hafiz Umer Javed (Food Hydrocolloids, 2025)

Constructing an in situ biomimetic basement membrane within tumor tissue to disrupt intercellular adhesion molecule communication and prevent metastasis in TNBC - Jianing Ji; Ping Zeng; Jiade Yang; Fuan Deng; Fengyi Wang; Yuxiang Xiong; Hualing Li; Xiaojia Chen; Chunping Mao; Lu Zhang (Chemical Engineering Journal, 2025)

Toxic effects of enrofloxacin on grass carp (Ctenopharyngodon idellus): an ecological risk assessment based on cross-system regulatory mechanisms and network toxicology - Ping Li; Bianhao Zeng; Xuqian Cao; Yiwei Liu; Cheng-Zhuang Chen; Bin Liu; Ling Liu; Yi Chai; Zhi-Hua Li (Aquatic Toxicology, 2025)

Discovering novel type I collagen fragments from Cyprinus carpio supporting bone regeneration - Jianhua Zeng; Miao Chen; Xinglong Wang; Huan Yu; Liang Zhang; Yongxing Peng; Ping Wan; Zhongshi Huang; Fuqiang Ma; Jingtang Li (Functional & Integrative Genomics, 2025)

Solar-activated ZnS@MXene heterostructure for integrated radioactive wastewater treatment and energy harvesting - Yi-Lin Liu; Ping Cao; Qingyan Zhang; Changgui Guo; Jing Li; Qingyi Zeng (Water Research, 2025)

Novel umami peptides from Grass Carp marinated with Red Yeast Rice Flour and their taste presentation mechanisms characterized by in silico approach and sensory evaluation - Qiaohui Zeng; Miaoshan Zhou; Lifang Gao; Ping Qi; Shilin Cao; Jian Li; Xinan Zeng; Jingjing Wang (Food Bioscience, 2025)

Multi-omics and random forest reveal lipid metabolism disruption and biomarkers in grass carp (Ctenopharyngodon idellus) exposed to 2-methylisoborneol - Huan Han; Jun-Ming Zhang; Kang Li; Justice Frimpong Amankwah; Xiang-Biao Zeng; Zi-Qian Shen; Xi-Chen Jin; Tao-Ying Chen; Jing-Wei Liu; Li-Ping Liu (Environmental Research, 2025)

Synergistic cation-anion interface engineering for uniform zinc deposition and stress mitigation in reinforced Zn metal anodes - Yixing Fang; Ping Li; Feng Sun; Chuyuan Lin; Xiao Yang; Zhen Wang; Guodong Miao; Lingxing Zeng; Yongchang Liu; Xuanhui Qu (Chemical Engineering Journal, 2025)

Synergistic dual-Lewis sites in cobalt-doped Fe3S4 for enhanced hydrogen peroxide activation and contaminant degradation - Li-Ping Jin; Fan Zhou; Qin Liu; Su-Qin Wang; Meng-Meng Zeng; Xin-Yu Huang; Li Liu; Xiao-Han Yu; Mei-Feng Wu; Jian-Ping Zou (Chemical Engineering Journal, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

Defining a Triassic carbonatite-related Mo-(REE) metallogenic belt along the southern margin of the North China Craton - Sheng-Ren Chang; Xin-Fu Zhao; Jian-Hui Su; Shao-Rui Zhao; Li-Ping Zeng; Carl Spandler (Mineralium Deposita, 2025)

Crushing characteristics and energy dissipation modeling of Single-Particle-Size carbonaceous mudstone as roadbed fill - Yan Wang; Hong-yuan Fu; Jian-Ping Song; Ling Zeng; Tao Li; Jian-Ping Xiong; Hong-Ri Zhang; Wen-Guang Wang; You-Jun Li; Jing-Cheng Chen (Bulletin of Engineering Geology and the Environment, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Experimental and theoretical calculation study on phosphorus removal by nZVI-loaded biochar/active clay: Synergism of chemical bonding and coordination - Tong Hao; Chen Zhao; Mingyu Shan; Yubo Ding; Kongna Wu; Xing Dai; Juan Li; Ping Zeng (Journal of Environmental Chemical Engineering, 2025)

Highly efficient and selective uranium capture across wide concentration and pH ranges by graphitic carbon nitride with multiple Lewis base sites - Wenxiu Sun; Minjie Wang; Qinyan Zhang; Ping Cao; Qingyun Yang; Mi Li; Tao Cai; Qingyi Zeng (Journal of Environmental Chemical Engineering, 2025)

Black rice stepwise fermentation enhances yogurt gel quality: Solidification rate, texture, LAB distribution and viability persistence - Jiarui Zeng; Zhiming Wang; Guang Liu; Xuchao Jia; Pengfei Zhou; Ping Li; Zhihao Zhao; Yan Zhang; Xiaojun Tang; Dong Liu; Yuanyuan Deng; Mingwei Zhang (Food Chemistry, 2025)

Metagenomics-metabolomics integration reveals the impacts and action mechanisms of sulfamethoxazole in a continuous-flow aerobic granular sludge membrane bioreactor: System performance and microbial functional shifts - Wenqiang Xiong; Yu Zeng; Liying Bin; Weirui Chen; Xinyi Chen; Shanglong Wen; Shaosong Huang; Ping Li; Bing Tang (Chemical Engineering Journal, 2025)

The role of evaporites in Kiruna-type iron oxide-apatite deposits in the Northern Norrbotten region, Sweden: Evidence from in situ halogen analyses of scapolite - Li-Ping Zeng; Carl Spandler; Ying-Ying Liu; Johannes Hammerli; Wang Liao; Hao Hu; Sanna Olsson; De-Xian Zhang; Tao He; Jian-Wei Li; Xin-Fu Zhao (Chemical Geology, 2025)

Island Biogeography and Life‐History Traits Stabilize Island Bird Communities - Yuhao Zhao; Di Zeng; Thomas J. Matthews; Dylan Craven; Morgan W. Tingley; Shaopeng Wang; Shao‐peng Li; Ping Ding; Xingfeng Si (Global Change Biology, 2025)
Islands are model systems for testing and developing ecological theories. Despite extensive research on island biodiversity, the importance of the biogeographic context for biodiversity–stability relationships is poorly understood. We addressed this knowledge gap by integrating the Equilibrium Theory of Island Biogeography (ETIB) with a functional perspective to explore island biodiversity–stability relationships. We conducted annual breeding bird surveys across 36 land‐bridge islands in eastern China over 13 years. Using this long‐term dataset, we quantified avian temporal community stability (and its components of population stability and population asynchrony) and tested how island biogeographic factors (i.e., island area, isolation, colonization rates, and extinction rates) and biodiversity facets (i.e., species richness, average population size, and life‐history traits) interact to influence stability. We found larger islands supported higher species richness due to colonization–extinction dynamics and habitat heterogeneity, which in turn promote both population stability and asynchrony. In addition, larger islands harbored larger and individually more stable populations over time. In contrast, island isolation had a weak net effect on stability, as its positive and negative influences through different pathways balanced each other out. Furthermore, species with ‘fast’ life‐history traits, characterized by shorter generation times, contributed more to community stability. These findings clarify multiple pathways through which biogeographic factors shape avian community dynamics on islands. Our study thus illustrates how island biotas maintain community stability and provides insights for preserving biodiversity and ecosystem functioning in fragmented or island‐like landscapes facing rapid biodiversity loss in an era of global change.

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

The deficiencies in texture, organic matter distribution, and active mineral composition of reservoir sediments constrain the formation of healthy soils - Xun Tan; Sidong Zeng; Binglei Li; Shengjun Wu; Ping Huang; Zhong Chen; Xingxing He; Zhilin Huang; Jiwei Bai (Journal of Environmental Management, 2025)

Nanoparticles co-delivering double-stranded RNA and insecticide enhance control efficacy and overcome pest resistance - Chao Hu; Chang Yu; Jiaqing Li; Yuxi Liu; Qinghong Zeng; Hu Wan; Shun He; Yuting Li; Ping Gao; Yuntong Lv; Kunyan Zhu; Subba Reddy Palli; et al. (Chemical Engineering Journal, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

MY-1 promotes angiogenesis in the ischemic hindlimbs by regulating the stability of CDC42 via PSMD14 - Xian Ding; Yuxin Zhang; Yuting Zeng; Qianlin Li; Sijie Qiu; Ping Xiao; Xin Luo; Jiaping Chen; Qianwen Deng; Dehong Yang; Yanli Zhang; Wenjuan Yan (Angiogenesis, 2025)

Effects of heat treatment on the binding between the key aroma-active compounds in Zanthoxylum bungeanum oil and pork myofibrillar proteins (MPs) - Qin Xiang; Lijuan Yao; Jiao Zhou; Songling Li; Wei Zeng; Ping Liu (Food Chemistry, 2025)

Prediction method of train induced vibration source intensity based on generalized transfer function - Wuji Guo; Zhiping Zeng; Fushan Liu; Peicheng Li; Weidong Wang; Cheng Chang; Qiuyi Li; Ping Li (Soil Dynamics and Earthquake Engineering, 2025)

Cyclic trace enzymatic hydrolysis pretreatment enhances brown rice: Cooking and taste - Yuanyuan Deng; Pengfei Zhou; Ya Li; Ping Li; Zhihao Zhao; Jiajia Wang; Lihuang Zhong; Guang Liu; Mingwei Zhang; Dong Liu; Jiarui Zeng (Food Chemistry, 2025)

Wear particles-induced periprosthetic osteolysis from a new perspective based on single-cell RNA-seq: crosstalk of osteoblast PANoptosis and macrophage efferocytosis in osteoimmunology microenvironment - Jia-xuan Li; Jian-ping Wen; Shuan-ji Ou; Yu-dun Qu; Chang-liang Xia; Wen-jun Li; Yang Yang; Jia-bao Liu; Rong-shen Yang; Wei Zeng; Wei Zhang; Yun-fei Ma; et al. (Chemical Engineering Journal, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Effects of early-life F-53B exposure on thyroid function in juvenile rats: The role of the cAMP signaling pathway - Shen-Pan Li; Wen-Hui Zhao; Jing Zhang; Wen-Ting Jiang; Jia-Yi Zhu; Yi-Xin Luo; Ping Xiang; Michael Bloom; Pasi Jalava; Guang-Hui Dong; Xiao-Wen Zeng (Journal of Hazardous Materials, 2025)

Recognizing the state of aerobic granular sludge over its life-cycle in a continuous-flow membrane bioreactor with an artificial intelligence approach - Yu Zeng; Chenguang Zhao; Danling Ma; Liying Bin; Weirui Chen; Ping Li; Bing Tang (Journal of Environmental Management, 2025)

Effects of eugenol–tricaine composite anesthesia on live transportation of Chinese mitten crab (Eriocheir sinensis) - Lele Leng; Ping Zhang; Ziyi Yin; Kexiang Li; Hang Li; Xiaoqun Zeng; Yangying Sun; Daodong Pan (Food Bioscience, 2025)

Discovery of potent MD2 inhibitors by hierarchical virtual screening strategy and bioactivity evaluation - Lili Yang; Jialu Liu; Lei Di; Siming Tang; Ping Hu; Fang Wang; Zeng Li (Chemico-Biological Interactions, 2025)

Recent advances and future research directions in the study of land-atmosphere interaction in northern China since the beginning of the 21st century - Qiang Zhang; Rong Wang; Ping Yue; Hongyu Li; Sheng Wang; Jian Zeng; Liang Zhang; Zesu Yang; Suping Wang; Jie Zhang; Liang Qiao; Hongli Zhang; et al. (Science China Earth Sciences, 2025)

Discovery and configurations assignment of Ile/Leu-containing cyclic peptides with cytotoxic activity, Reniochpeptins A–D, from the marine sponge Reniochalina sp. - Shuai-Shuai Zhang; Zong-Mei Wu; Ying Wu; Ya-Jun Zeng; Yuan-Yuan Zhang; Xin-Li Lin; Si Zhang; Kai-Xuan Zhan; Hou-Wen Lin; Shu-Ping Wang (Phytochemistry, 2025)

Insight into the influence of slight air oxidation on the carbonization behavior of pitch/calcined coke mixture to deliver high-performance graphite blocks - Pei Gong; Chongwei Li; Jiao Tan; Ping Liu; Xun He; Yixing Chen; Xiaobin Zeng; Run Li; Chuanjun Tu (Fuel, 2025)

Impacts of Naphthenic Acids (NAs) Exposure on Soil Bacterial Community and Antibiotic Resistance Genes (ARGs) Dissemination - Qianzhi Zeng; Qiangwei Liu; Yunhong Pu; Ping Gong; Yuxin Li; Yanan Sun; Yiming Hao; Qing Yang; Yaxuan Wu; Bowen Yang; Shengnan Shi; Zheng Gong (Current Microbiology, 2025)

Graph-based pangenome provides insights into structural variations and genetic basis of metabolic traits in potato - Xiaoling Zhu; Rui Yang; Qiqi Liang; Yuye Yu; Tingting Wang; Li Meng; Ping Wang; Shaoyang Wang; Xianping Li; Qiongfen Yang; Huachun Guo; Qijun Sui; et al. (Molecular Plant, 2025)

Aberrance of GAP43/p-GAP43 Closely Associates with the Pathology of Neuron Loss in Prion-Infected Rodent Models - Xiao-Xi Jia; Cao Chen; Chao Hu; Yue-Zhang Wu; Zhi-Yue Chao; Jia-Feng Zeng; Ru-Han A.; Dong-Hua Zhou; Yuan Wang; Wei-Wei Zhang; Kang Xiao; Li-Ping Gao; et al. (Molecular Neurobiology, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

Sex-specific effects of triphenyltin on gut microbiota and intergenerational effects in marine medaka (Oryzias melastigma) - Ping Li; Bian-Hao Zeng; Shu-Wen He; Bin Liu; Cheng-Zhuang Chen; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Construction of non-noble decorated Z-scheme Bi-BiVO4-Bi12TiO20 for enhanced full solar-spectrum driven photocatalytic activity - Jinhai Li; Hongkai Huang; Pili Lu; Zao Zeng; Ping Zhang; Yongpeng Wang; Tianhao Li; Xiaocan Li; Changxiong Luo (Environmental Research, 2025)

The H2S-releasing multifunctional composite ionic liquid facilitates topical melittin delivery for psoriasis treatment through RONS scavenging and inflammation inhibition - Meng Zeng; Ping Deng; Qin Li; Qi Tang; Jixiang Li; Liangke Zhang (Chemical Engineering Journal, 2025)

Transforming behavior and removal mechanism of phosphorus from municipal wastewater in a continuous flow aerobic granular sludge-membrane bioreactor: Unveiling the functional genes associated with phosphorus metabolism - Bingduo Wang; Mengci Ni; Yu Zeng; Biao Yang; Lei Shang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Removal of sulfonamides by persulfate-based advanced oxidation: A mini review - Juan Li; Xiangtian Peng; Ping Zeng; Liang Shen; Mingyue Li; Yanfei Guo (Chemosphere, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Defect confinement in CuO/HZSM-5-T catalysts: A novel approach for enhancing stability in AsH3 catalytic oxidation - Xinyu Yang; Ziruo Zeng; Zhao Li; Yaxi Zhang; Wei Mao; Zhongxian Wang; Xin Sun; Kai Li; Fei Wang; Ping Ning (Fuel, 2025)

Regulating heat-induced fibrous whey protein-wheat starch composite emulsion gels as dysphagia food by preheating temperature: Insights from protein-starch interactions - Zhiming Wang; Jiarui Zeng; Yuanyuan Deng; Pengfei Zhou; Ping Li; Zhihao Zhao; Guang Liu; Mingwei Zhang (Food Hydrocolloids, 2025)

Evaluation of Potentially Toxic Metal Bioaccumulation in Farmed Mussels: Assessing the Non-Contributory Role of Attachment Ropes in Metal Enrichment - Wei Ma; Xuelian Wei; Fenglian Zeng; Ming Li; Ping Wang; Jiji Li (Bulletin of Environmental Contamination and Toxicology, 2025)

Key process of ethanol hydrogen donor promoting the conversion of organic matter in sludge to bio-oil - Quxiu Dai; Linglong Zeng; Qihong Cen; Wang Du; Ping Ning; Kai Li; Zhiying Guo; Ran Ao; Longgui Xie; Nanqi Ren; Liping Ma; Jie Yang; et al. (Water Research, 2025)

Abundant surface adsorbed oxygen species originated from defect/vacancy sites during preferential CO oxidation - Yang Liu; Kunming Hou; Zhihua Guo; Yan Guo; Yue Jiang; Xinya Wu; Zewei Fu; Heng Zhang; Ping Li; Shanghong Zeng (Chemical Engineering Journal, 2025)

In situ reactivation of aerobic granular sludge in a membrane bioreactor after long-term storage: Revealing the variation in metabolic pathways under restored bioactivity - Yu Zeng; Bingduo Wang; Liying Bin; Weirui Chen; Ping Li; Xinyi Chen; Shanglong Wen; Shaosong Huang; Bing Tang (Chemical Engineering Journal, 2025)

Advancing plant disease classification: A robust and generalized approach with transformer-fused convolution and Wasserstein domain adaptation - Muhammad Hanif Tunio; Jian ping Li; Xiaoyang Zeng; Awais Ahmed; Syed Attique Shah; Hisam-Uddin Shaikh; Ghulam Ali Mallah; Imam Abdullahi Yahya (Computers and Electronics in Agriculture, 2024)

Pollution status and assessment of seven heavy metals in the seawater and sediments of Hangzhou Bay, China - Rong Zhu; Yan-Yan Zeng; Li-Min Liu; Lu Yin; Kai-Ping Xu; Wei-Feng Chen; Shang-Chun Li; Xiao-Feng Zhou (Marine Pollution Bulletin, 2024)

Effects of single or combined exposure to tralopyril and ocean acidification on energy metabolism response and sex development in Pacific oysters (Crassostrea gigas) - Ping Li; Minghao Yin; Xu Wang; Ruolan Jia; Chengzhaung Chen; Bin Liu; Yiwei Liu; Bianhao Zeng; Tengzhou Li; Ling Liu; Hong-Jun Song; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

MoS2 coupled with ball milling co-modified sludge biochar to efficiently activate peroxymonosulfate for neonicotinoids degradation: Dominant roles of SO4•-, 1O2 and surface-bound radicals - Yifan Liu; Yongfei Ma; Zhikang Deng; Ping Li; Song Cui; Chenyu Zeng; Rui Mu; Yusheng Zhou; Xuebin Qi; Zulin Zhang (Environmental Research, 2024)

CD36-mediated ROS/PI3K/AKT signaling pathway exacerbates cognitive impairment in APP/PS1 mice after noise exposure - Zan Zhou; Wen-jun Jiang; Yan-ping Wang; Jun-qiang Si; Xian-si Zeng; Li Li (Science of The Total Environment, 2024)

Anionic surfactant-activated remediation of Pb, Cd, As contaminated soil by electrochemical technology - Ping Zhang; Penggang Li; Yang Ping; Hao Xu; Zhenzhou Zhang; Feiping Zhao; Gai Zeng; Peicheng Huang; Zhihui Yang (Science of The Total Environment, 2024)

In situ reconstruction of multi-phase heterostructured anodes for efficient and durable solid oxide fuel cells - Tian Gan; Bin Sheng; Quanyu Zeng; Yuchen Li; Yujun Han; Wenya Zhen; Ping Li; Yongdan Li (Chemical Engineering Journal, 2024)

Tissue-Specific Toxicity in Common Carp (Cyprinus carpio) Caused by Combined Exposure to Triphenyltin and Norfloxacin - Yiwei Liu; Luoxin Li; Siqi Zhang; Minghao Yin; Tengzhou Li; Bianhao Zeng; Ling Liu; Ping Li; Zhihua Li (Fishes, 2024)
Triphenyltin (TPT) is a commonly encountered organotin compound known for its endocrine-disrupting properties; it frequently interacts with antibiotics in aquatic environments. In this study, common carp (Cyprinus carpio) (17.43 ± 4.34 g, 11.84 ± 0.88 cm) were chosen as the experimental organisms. According to the environmental concentration in the heavily polluted area, the control group and the experimental groups were exposed for 21 days to the following treatments: 1 μg/L TPT, 1 mg/L NOR, and a combination of 1 μg/L TPT plus 1 mg/L NOR. The investigation examined the individual and combined toxicities of TPT and norfloxacin (NOR) on the gill, liver, and gut tissues of common carp in highly polluted areas. The findings revealed tissue-specific variations in 1L-1β enzyme activity; specifically, 1L-1β enzyme activity exhibited a significant reduction in liver tissue under both NOR exposure and combined exposure, indicating that high concentrations of NOR had the most pronounced impact on the immune system of liver tissue. Furthermore, the gene expression levels of IL-1β, Lysozyme-C, NKA, and CPT1 in the liver, intestinal, and gill tissues showed differences after exposure. In addition, TPT exerted the most significant effect on intestinal tissue, followed by the liver and gill tissues. Interestingly, when TPT and NOR were exposed together, the toxic effects on all tissues were reduced, suggesting the existence of antagonistic effects.

Conjugates of glycosylated antarctic krill proteins and curcumin: Maintaining the storage quality of salmon fillets coupling with photodynamic inactivation - Qiaohui Zeng; Di Hu; Yufeng Li; Ping Qi; Lu Chen; Ronghan Wang; Yong Zhao; Jing Jing Wang (Food Hydrocolloids, 2024)

Mn doping and core-shell engineering of silane-modified Mn-TiO2@SiO2 nanoparticles with drastically reduced photocatalytic activity for transparent UV-shielding hybrid materials - Xiangyu Tian; Xinuo Cai; Zixu Zeng; Yi He; Xijun Xu; Lecheng Lei; Cheng Xu; Xin Xu; Yongfeng Xu; Ping Li; Xingwang Zhang (Chemical Engineering Journal, 2024)

Triarylamine-based polyimide COFs for achieving high performance ambipolar multi-color electrochromic energy-storage films - Lei Huang; Rong Guo; Qingqing Qiu; Huan Li; Putrakumar Balla; Jinming Zeng; Tongxiang Liang; Xiaopeng Qi; Ping Liu (Chemical Engineering Journal, 2024)

Multifunctional and immunoregulatory microenvironment-responsive hydrogel for whole course management of infected diabetic wounds - Zhenyu Luo; Xiaoxue Fu; Hua Jiang; Weikun Meng; Shue Jin; Yongrui Cai; Ze Du; Ping Song; Anjing Chen; Li Li; Peifang Li; Jiali Chen; et al. (Chemical Engineering Journal, 2024)

Rich-silicon rice husk ash increases iron plaque formation and decreases cadmium and arsenic accumulation in rice seedlings - Jiao-Feng Gu; Xuan-Tao Yi; Kun Ouyang; Qian Li; Ping You; Rui Zhou; Peng Zeng; Ye Liao; Hang Zhou (Chemosphere, 2024)

Impacts of environmental regulation perceptions on farmers’ intentions to adopt multiple smart hog breeding technologies: Evidence from rural Hubei, China - Yangmei Zeng; Ke He; Junbiao Zhang; Ping Li (Journal of Cleaner Production, 2024)

An investigative study on the resistance characteristics and vertical stiffness of the novel recycled rubber composite sleeper in a ballasted track structure - Ayoub A.S. Qahtan; Zhiping Zeng; Mengxuan Ye; Ping Li; Qiuyi Li; Weidong Wang; Xuejun Li (Engineering Structures, 2024)

The impact of dissipative algorithms on assessment of high-speed train running safety on railway bridges - Han Zhao; Biao Wei; Zhanjun Shao; Xiaonan Xie; Peng Zhang; Huifang Hu; Yingying Zeng; Lizhong Jiang; Changqing Li; Ping Xiang (Engineering Structures, 2024)

Efficient degradation of sulfadiazine by UV-triggered electron transfer on oxalic acid-functionalized corn straw biochar for activating peroxyacetic acid: Performance, mechanism, and theoretical calculation - Chenyu Zeng; Yongfei Ma; Ping Li; Xi Chen; Hongtao Liu; Zhikang Deng; Rui Mu; Xuebin Qi; Zulin Zhang (Bioresource Technology, 2024)

Molecular characterization of fad6 gene and its transcriptional changes in response to different initial diets and nutritional status in yellow catfish (Pelteobagrus fulvidraco) - Bo Zhou; Xiu-Ying Wei; Zheng-Yong Wen; Bin Wang; Yu-Ying Zhao; Wan-Hong Zeng; Yu He; Panita Prathomya; Yun-Yun Lv; Yan-Ping Li; Jun Wang; Rui Li; et al. (Frontiers in Marine Science, 2024)
Fatty acid desaturases (FADs) are rate-limiting enzymes for the biosynthesis of highly unsaturated fatty acids (HUFAs). As a new member of the FAD family, Fad6 and its roles remain unclear in various teleost fishes. In this study, we identified a fad6 gene from yellow catfish (yc fad6 ) and determined its spatiotemporal expression patterns and responses to different initial diets and nutritional status in yellow catfish. Our results showed that the open reading frame (ORF) of yc fad6 was 1,080 bp in length, encoding a protein of 359 amino acids. Multiple protein sequences alignment proved that fad6 is highly conserved among diverse vertebrates. Meanwhile, phylogenetic analysis revealed that Southern catfish and yellow catfish were clustered into one branch, supporting evolutionary consistence between the fad6 gene and fish morphology. Moreover, comparisons of genomic synteny and gene structure revealed functional and evolutionary conservation of the fad6 gene in various teleost fishes. Tissue distribution analysis by quantitative RT-PCR demonstrated that the yc fad6 gene was extensively expressed in examined tissues, with higher transcription levels in the heart and liver. Meanwhile, yc fad6 gene was widely expressed in various developmental stages, indicating Fad6 may play important roles in HUFA biosynthesis at early developmental stages in yellow catfish. Functional experiments verified that the transcription of yc fad6 decreased significantly with the extension of feeding time (with egg yolk or Artemia nauplii ) at the early developmental stages, indicating that a diet rich in HUFA can remarkably inhibit the transcription of yc fad6 in yellow catfish. In addition, yc fad6 transcription was significantly reduced after a short-term (24-h) or long-term food deprivation (1-week) and then continued to decrease during refeeding, suggesting that nutritional states can affect the transcription of yc fad6 , which further regulates the metabolism of HUFAs. Anyway, these fundamental findings provide basic references for further investigating evolutionary and physiological functions of the fad6 gene in yellow catfish as well as in other teleost fishes.

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Inhibition of flowering by gibberellins in the woody plant Jatropha curcas is restored by overexpression of JcFT - Ping Huang; Jie Yang; Jiapeng Ke; Li Cai; Yingxiong Hu; Jun Ni; Chaoqiong Li; Zeng-Fu Xu; Mingyong Tang (Plant Science, 2024)

Medial amygdala NRG1 signaling mediates adolescent social isolation-induced autistic-like behaviors - Lian-Hong Lin; Qian-Yun Wu; Kai Zeng; Zi-Yu Chen; Zi-Ping Wang; Wei-Min Li; Bin Zhang; Tian-Ming Gao; Ji-Hong Liu (Science Bulletin, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

Geochemistry and P-T-t evolution of Paleoproterozoic metapelites of the Zhengjiapo BIF-type iron mine, Jiaobei terrane, North China Craton - Yan-Rong Chen; Xu-Ping Li; Zeng-Sheng Li; Da-Peng Li; Fan-Mei Kong; Hans-Peter Schertl; Yan-Jing Chen (Precambrian Research, 2024)

Exosome-functionalized heterogeneous nanofibrous scaffolds repair bone defects accompanied by muscle injury - Shue Jin; Zeyu Luo; Yongrui Cai; Jing Wen; Pengyu Lu; Xiaoxue Fu; Ping Mou; Anjin Chen; Weikun Meng; Jidong Li; Zongke Zhou; Weinan Zeng (Chemical Engineering Journal, 2024)

Iron oxide–apatite deposits form from hydrosaline liquids exsolved from subvolcanic intrusions - Xin-Fu Zhao; Li-Ping Zeng; Wang Liao; Yi-Zhe Fan; Albert H. Hofstra; Poul Emsbo; Hao Hu; Guang Wen; Jian-Wei Li (Mineralium Deposita, 2024)

LiCOI1 mediates the biosynthesis of monoterpenes induced by methyl jasmonate in Lilium ‘Siberia’ - Zhuo Leng; Ying-Ying Li; Yu-Chen Fu; Jing Wu; Ping-Sheng Leng; Zeng-Hui Hu (Horticulture, Environment, and Biotechnology, 2024)

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Promoted iron corrosion and subsequent hexavalent chromium removal in zero-valent iron systems by oxidant activation - Weiting Chen; Bing Li; Weizhao Yin; Weilong Zeng; Ping Li; Jinhua Wu (Chemosphere, 2024)

Co-occurrence of organophosphate esters and phosphorus fractions in river sediments: Implications for pollution prediction and environment risk assessment - Lingfang Fu; Yuxin Liu; Shu Lin; Jieer Xiao; Weijie Li; Yang Yu; Hailong Zeng; Ping Li; Huaiyang Fang (Journal of Hazardous Materials, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Charge-reversal biodegradable nanoplatform with ferroptosis and ICD induction for tumor synergistic treatment - Ping Sun; Li Huang; Zimu Li; Yao Yang; Shiman Lu; Nansha Gao; Hongzhong Chen; Xiaowei Zeng; Zhongjian Xie (Chemical Engineering Journal, 2024)

Genetic Composition of the High-Quality Winter Wheat Varieties ‘Xinmai 26’ and ‘Xinmai 45’ - Li-Juan Yang; Jian Ma; Da-Le Zhang; Hai-Feng Yang; Yan-Qi Dong; Zeng-Jun Qi; Meng-Jiao Li; Zhi-Kai Jiang; Hua-Ping Ma (Plant Molecular Biology Reporter, 2024)

Metabolomics analysis to interpret changes in physiological and metabolic responses to chronic heat stress in Pekin ducks - Xiangyi-Yi Zeng; Arshad Javid; Gang Tian; Ke-Ying Zhang; Shi-Ping Bai; Xue-Mei Ding; Jian-Ping Wang; Li Lv; Yue Xuan; Shan-Shan Li; Qiu-Feng Zeng (Science of The Total Environment, 2024)

Large-scale offshore wind energy integration by wind-thermal bundled power system: A case study of Yangxi, China - Runzhao Li; Xiaoming Jin; Ping Yang; Yimin Feng; Yun Liu; Shichao Wang; Xiaoliang Ou; Pengxiao Zeng; Yaoneng Li (Journal of Cleaner Production, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Rosmarinic acid against cognitive impairment via RACK1/HIF-1α regulated microglial polarization in sepsis-surviving mice - Dan-yang Liu; Yao Wu; Zi-qi Feng; Yang Yu; Hua-wei Cai; Shi-ping Liao; Tao Zeng; Ling Zhu; Xia Wang; Li-hong Wan (Chemico-Biological Interactions, 2024)

Effects of single and combined contamination of total petroleum hydrocarbons and heavy metals on soil microecosystems: Insights into bacterial diversity, assembly, and ecological function - Du Zhang; Qi Hu; Bing Wang; Junwen Wang; Can Li; Ping You; Rui Zhou; Weimin Zeng; Xueduan Liu; Qian Li (Chemosphere, 2023)

Sediment depth-related variations of comammox Nitrospira: Evidence in the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ziqiang Mao; Ping Huang; Shengjun Wu (Science of The Total Environment, 2023)

Beyond filterability: Understanding the complexities of sludge dewatering through typical coagulation and advanced oxidation - Wen-Hui Liu; Hao Zhang; Ya-Li Zhang; Ping Sun; Yuan-Ping Zeng; Yun-Yan Gao; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Cleaner Production, 2023)

Identifying priority PBT-like compounds from emerging PFAS by nontargeted analysis and machine learning models - Bao-Cang Han; Jin-Song Liu; Aaron Bizimana; Bo-Xuan Zhang; Sukhodolska Kateryna; Zhen Zhao; Li-Ping Yu; Zhong-Zeng Shen; Xiang-Zhou Meng (Environmental Pollution, 2023)

Oleyl Phosphate-Modified Crystalline-Amorphous TiO2/Ce2O3 heterojunction nanoparticles with significantly reduced photocatalytic activity as stable UV-Shielding fillers - Xiangyu Tian; Weiwei Han; Zixu Zeng; Yi He; Lecheng Lei; Xijun Xu; Xin Xu; Yongfeng Xu; Ping Li; Xingwang Zhang (Chemical Engineering Journal, 2023)

Interfacial adsorption of gold nanoparticles on arsenian pyrite: New insights for the transport and deposition of gold nanoparticles - Xin Nie; Quan Wan; Michael F. Hochella; Suxing Luo; Meizhi Yang; Shanshan Li; Yuhong Fu; Ping Zeng; Zonghua Qin; Wenbin Yu (Chemical Geology, 2023)

17β-Estradiol Mediates Staphylococcus aureus Adhesion in Vaginal Epithelial Cells via Estrogen Receptor α-Associated Signaling Pathway - Lina Yan; Can Rui; Bin Zhuang; Xia Liu; Ting Luan; Lisha Jiang; Zhiyong Dong; Qing Wang; Aiwen Wu; Ping Li; Xinyan Wang; Xin Zeng (Current Microbiology, 2023)

Cytotoxic phenyl polyketides from Hypericum curvisepalum N. Robson - Qiu-Ying He; Hong Zeng; Qiu-Lan Zhang; Guan-Fang Qin; He-Bin Wang; Li-Ping Teng; Zhong-Bo Zhou (Natural Product Research, 2023)

Enhancing data reliability in quantitative characterization of moisture distribution in sludge using DSC: Impact of sample attributes and test parameters - Ya-Li Zhang; Hao Zhang; Wen-Hui Liu; Ping Sun; Shao-Ming Zheng; Yun-Yan Gao; Yuan-Ping Zeng; Hou-Feng Wang; Raymond Jianxiong Zeng (Journal of Environmental Management, 2023)

Vertical variation in prokaryotic community composition and co-occurrence patterns in sediments of the Three Gorges Reservoir, China - Baohong Yu; Quanchao Zeng; Jinlin Li; Jun Li; Xun Tan; Xin Gao; Ping Huang; Shengjun Wu (Environmental Research, 2023)

Paternal cadmium exposure induces glucolipid metabolic reprogramming in offspring mice via PPAR signaling pathway - Ling Zeng; Jinzhao Zhou; Yanwei Zhang; Xiaofei Wang; Yamin Li; Jieping Song; JingFan Shao; Ping Su (Chemosphere, 2023)

A momentum-based prediction model of backwater rise within and downstream of an emergent canopy in nonuniform flow - Ping Wang; Yonggang Zhang; Jinhua Cheng; Huilan Zhang; Li Zeng (Journal of Hydrology, 2023)

Experimental research progress of grid to rod fretting in pressurized water reactors - Yong-jun Jiao; Zheng-yang Li; Zeng-ping Pu; Mei-yin Zheng; Quan-yao Ren; Zhen-bing Cai; Yin-wei Wu; Sui-zheng Qiu (Annals of Nuclear Energy, 2023)

In situ deposition of double Fe-based Fenton catalysts on the porous membrane for the development of multi-defense against various foulants toward highly efficient water purification - Yu-Ling Yang; Gang Wang; Ping Zhu; Lei Tang; Zhi-Xiang Zeng; Li-Jing Zhu (Chemical Engineering Journal, 2023)

Functional characterization of novel NPRL3 mutations identified in three families with focal epilepsy - Shiyue Du; Sheng Zeng; Li Song; Hongying Ma; Rui Chen; Junyu Luo; Xu Wang; Tingbin Ma; Xuan Xu; Hao Sun; Ping Yi; Jifeng Guo; et al. (Science China Life Sciences, 2023)

Efficient lipid synthesis of Chlorella pyrenoidosa promoted under heavy metals from electric arc furnace slag - Qing Yu; Tian-Ji Liu; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Yu-Ran Wang; Le-Le Kang; Rui Ji; Fu-Ping Wang; Xiao-Man Wang; Bao Liu; Shuang Cai; et al. (Journal of Cleaner Production, 2023)

Iron isotope fractionation during fluid metasomatism and ore-forming processes in magmatic-hydrothermal systems - Wang Liao; Xin-Fu Zhao; Li-Ping Zeng; Stefan Weyer; Chao Zhang; Ingo Horn; Francois Holtz (Geochimica et Cosmochimica Acta, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Contamination characteristics and source analysis of potentially toxic elements in dustfall-soil-crop systems near non-ferrous mining areas of Yunnan, southwestern China - Ying Luo; Zhe Wang; Zhen-Long Zhang; Jia-Qian Zhang; Qiu-Ping Zeng; Duan Tian; Chao Li; Feng-Yu Huang; Shu Chen; Li Chen (Science of The Total Environment, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

What affects the accuracy and applicability of determining wastewater sludge water content via low-field nuclear magnetic resonance? - Ya-Li Zhang; Ping Sun; Bing-Bing Dai; Shao-Ming Zheng; Dan-Di Ran; Tian-Xin Wu; Raymond Jianxiong Zeng; Hou-Feng Wang (Environmental Research, 2023)

Adoption and ex-post impacts of sustainable manure management practices on income and happiness: Evidence from swine breeding farmers in rural Hubei, China - Yangmei Zeng; Ke He; Junbiao Zhang; Ping Li (Ecological Economics, 2023)

Simultaneously achieving enhanced water adsorption and rapid adsorbed hydroxyl transfer toward MXene-based materials for highly efficient alkaline electrocatalytic hydrogen evolution - Yang Meng; Ping Zeng; Xiao-Yu Yang; Zhan Liu; Xiao-Yun Li; Cui-Fang Ye; Yu Li; Jin-Ping Liu; Bao-Lian Su; Li-Hua Chen; Yi-Long Wang (Chemical Engineering Journal, 2023)

Late Carboniferous extension-related magmatism in the southwestern Alxa block of NW China: geochronology, geochemistry, and tectonic implications - Zeng-Zhen Wang; Xuan-Hua Chen; Wei-Cui Ding; Bing Li; Yi-Ping Zhang; Zhao-Gang Shao; Sheng-Lin Xu (International Geology Review, 2023)

Overestimation of 1O2 role in N-doped carbon materials/peroxymonosulfate system: The misleading of furfuryl alcohol quenching effect - Liangjie Wang; Juan Li; Xinyao Liu; Jiali Zhang; Ping Zeng; Yonghui Song (Chemosphere, 2023)

Effects of obstacles inside the tube on initial self-ignition of high-pressure hydrogen release through a tube - Ping Li; Qian Zeng; Qiangling Duan; Xianfeng Chen; Jinhua Sun (Fuel, 2023)

Extracellular Vesicles Derived from Bone Mesenchymal Stem Cells Carrying circ_0000075 Relieves Cerebral Ischemic Injury by Competitively Inhibiting miR-218-5p and Up-regulating E3 Ubiquitin Ligase SMURF2 - Yue Liu; You-Ping Li; Li-Min Xiao; Li-Ke Chen; Su-Yue Zheng; Er-Ming Zeng; Chun-Hua Xu (Molecular Neurobiology, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Correction to: Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2023)

Investigation of the relationship between MBP gene polymorphisms and delayed encephalopathy after acute carbon monoxide poisoning - Fan Zhang; Jiao Zeng; Xiaoli Zhang; Jiapeng Gu; Yongkai Han; Ping Zhang; Wenqiang Li; Renjun Gu (NeuroToxicology, 2023)

Ultra-depleted melt product preserved in the Ladong ophiolitic peridotites of the North Qilian Orogenic Belt, Northern Tibet - Xiang Zhou; Jian-Ping Zheng; Zeng-Bao Huang; Zhi-Yong Li; Wei-Qi Zhang; Hong-Da Zheng; Qing Xiong; Hong-Kun Dai (Lithos, 2023)

Highly efficient removal of hexavalent chromium by magnetic Fe–C composite from reed straw and electric furnace dust waste - Fu-Ping Wang; Ya-Nan Zeng; Yi-Tong Wang; Jun-Guo Li; Xi Zhang; Ai-Min Ji; Le-Le Kang; Rui Ji; Qing Yu; Di Gao; Xiao-Man Wang; Zhen Fang (Environmental Science and Pollution Research, 2022)

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Caffeine alleviates acute liver injury by inducing the expression of NEDD4L and deceasing GRP78 level via ubiquitination - Xing-Wang Hu; Xiang-Min Li; Ai-Min Wang; Yong-Ming Fu; Fang-Jie Zhang; Feng Zeng; Li-Ping Cao; Hui Long; Ying-Hui Xiong; Ji Xu; Jia Li (Inflammation Research, 2022)

Streptomyces: Derived Active Extract Inhibits Candida albicans Biofilm Formation - Sheng-qiang Yang; Hui-jie Zhou; Li-ping Teng; Hong Zeng (Current Microbiology, 2022)

Study on the Effectiveness and Mechanism of Mercapto-Modified Attapulgite for Remediation of Cadmium-Contaminated Paddy Soil - Guangxi He; Xiaping Zhu; Yan An; Yuying Chen; Cheng Fu; Ningfei Lei; Ying Zeng; Junya Li; Zepeng Wang; Ping Zhao (Water, Air, & Soil Pollution, 2022)

Integrated genetic mapping and transcriptome analysis reveal the BnaA03.IAA7 protein regulates plant architecture and gibberellin signaling in Brassica napus L. - Xiaoke Ping; Qianjun Ye; Mei Yan; Jianyan Zeng; Xingying Yan; Haitao Li; Jiana Li; Liezhao Liu (Theoretical and Applied Genetics, 2022)

Adventitious bud regeneration and Agrobacterium tumefaciens-mediated genetic transformation of Eucalyptus urophylla × E. tereticornis interspecific hybrid - Xiaoping Wang; Ping Luo; Zhenfei Qiu; Xiaodan Li; Bingshan Zeng; Chunjie Fan (In Vitro Cellular & Developmental Biology - Plant, 2022)

A landscape‐level analysis of bird taxonomic, functional and phylogenetic β‐diversity in habitat island systems - Chi Zeng; Wande Li; Ping Ding; Yu Peng; Lingbing Wu; Xingfeng Si (Journal of Biogeography, 2022)
Aim How β‐diversity patterns are shaped by landscape‐level processes remains unclear across habitat island systems. Here we assessed landscape‐level bird β‐diversity in habitat island systems and aimed to (1) evaluate the relative contribution of turnover (β SIM ) and nestedness‐resultant (β SNE ) components to multisite β‐diversity (β SOR ) from taxonomic, functional and phylogenetic dimensions; (2) examine the influence of climate factors and system characteristics in shaping landscape‐level patterns of β‐diversity measures; and (3) study how β‐diversity patterns of bird communities vary with the spatial extents of island systems. Location Global. Taxon Birds. Methods We compiled bird data in 22 habitat island systems from literature and classified these island systems into small and large spatial scales. We partitioned β SOR into β SIM and β SNE from three dimensions for each system and calculated standardized functional and phylogenetic β‐diversity measures. We assessed the effects of climate factors and system characteristics on observed and standardized β‐diversity measures by multiple linear models for both small and large systems. Results We found that the dominant role of β SIM to β SOR in habitat island systems was pervasive. However, the best explanatory variables were not consistent across systems, which depended on the β‐diversity components, diversity dimensions and spatial extent of habitat island systems. In general, climate factors acted as the main drivers of bird communities across small and large systems, whereas system characteristics played minor roles. Main conclusions Spatial turnover dominated overall bird β‐diversity in most habitat island systems. Our results imply the roles of niche‐based assembly processes through the interplay among differential functional traits and phylogenetic distances of species, climate factors and system characteristics as well as spatial extent in driving bird communities across multiple habitat island systems at a landscape level. This study offers a better understanding of the processes underlying macroecological patterns of isolated biological communities across habitat island systems.

MiR-1260b protects against LPS-induced degenerative changes in nucleus pulposus cells through targeting TCF7L2 - Shijie Chen; Guixia Shi; Jin Zeng; Ping Huang Li; Yi Peng; Zhiyu Ding; Hong Qing Cao; Ruping Zheng; Weiguo Wang (Human Cell, 2022)

Urinary phthalate metabolites in pregnant women: occurrences, related factors, and association with maternal hormones - Wei Wu; Zhi-li Ma; Fang Yang; Ping Wu; De-xin Zhang; Rong Zeng; Dan-ling Sun; Liu Cao (Environmental Science and Pollution Research, 2022)

Preparation and In Vitro and In Vivo Evaluation of a Testosterone Film Forming Gel for the Treatment of Hypoactive Sexual Desire Disorder in Women - Jia Zeng; Tan-Fang Xie; Ting Huang; Fang Li; Zhi-Ping Wang; Ling-Lin Feng (AAPS PharmSciTech, 2022)

Biological monitoring and health assessment of 21 metal(loid)s in children and adolescents in Liuzhou City, Southwest China - Yaping Li; Yu Zhang; Meng Yu; Liqin Hu; Ting Zeng; Ling Liu; Limei Wang; Liangqiong Deng; Xiang Li; Ping Liu; Dingyuan Zeng; Surong Mei (Environmental Science and Pollution Research, 2022)

A contribution to knowledge of Gyroporus (Gyroporaceae, Boletales) in China: three new taxa, two previous species, and one ambiguous taxon - Hui-Jing Xie; Li-Ping Tang; Man Mu; Yu-Guang Fan; Shuai Jiang; Ming-Sheng Su; Zhi-Qun Liang; Nian-Kai Zeng (Mycological Progress, 2022)

Antifungal Effect of Long Noncoding RNA 9708-1 in the Vulvovaginal Candidiasis Murine Model - Ying Wu; Lisha Jiang; Lingling Zhang; Xia Liu; Lina Yan; Ting Luan; Can Rui; Zhiyuan Mao; Chong Fan; Yu Liu; Ping Li; Xin Zeng (Mycopathologia, 2021)
Vulvovaginal candidiasis (VVC) caused by Candida spp. affects 70–75% of women at least once during their lives. We aim to elucidate the potential mechanism of VVC and investigate the therapeutic effects of long noncoding RNA 9708-1. Female BALB/c mice were randomized to four treatment groups, including the blank control group, VVC control group, vehicle control group and lncRNA 9708-1-overexpressed group. Mice were euthanized on Day 4, Day 7 and Day 14 after treatment. Colony-forming unit (CFU) was measured, and the inflammation was detected by hematoxylin and eosin (H&E). Gene and protein expression levels of lncRNA 9708-1 and FAK were determined by real-time PCR, Western blot and immunohistochemistry. The overexpression of lncRNA 9708-1 significantly decreased the fungal load from Day 4 to 7. H&E staining indicated that the impaired histological profiles were improved in lncRNA 9708-1-overexpressed group. LncRNA 9708-1 led to a significant increase in FAK level of vagina tissue which is expressed mainly in epithelial basal layer. This study suggests that lncRNA 9708-1 played a protective role on murine experimental VVC by upregulating the expression levels of FAK.

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

Mutation of iPGAM using the CRISPR/Cas9 system affects pollen vitality and chlorophyll synthesis in Nicotiana tabacum - Lijing Liu; Ling Jia; Li Xu; Lele Deng; Ping Zhao; Wanli Zeng (Plant Biotechnology Reports, 2021)

Association of ADH7 Gene Polymorphism with Schizophrenia in the Han Population of Northern China: a Case-Control Study - Kuo Zeng; Ya Li; Meng Gao; Yong-ping Liu; Feng-ling Xu; Xi Xia; Jun Yao; Bao-jie Wang (Journal of Molecular Neuroscience, 2020)

Model test of the stability degradation of a prestressed anchored rock slope system in a corrosive environment - Cong Li; Rong-tang Zhang; Jie-bing Zhu; Zhi-jun Liu; Bo Lu; Bin Wang; Yu-zhou Jiang; Jie-sheng Liu; Ping Zeng (Journal of Mountain Science, 2020)

Chopper Sugarcane Combine Harvester with Middle-Mounted Primary Extractor - Tao Wu; Xiao-Ling Liang; Qing-Ting Liu; Zeng-Xue Zhang; Hai Xu; Ji-Bai Huang; Jin-Xin Li; Xiao-Ping Zou (Sugar Tech, 2020)

The Role of 17β-Estrogen in Candida albicans Adhesion on Human Vaginal Epithelial Cells via FAK Phosphorylation - Ting Luan; Xia Liu; Pengyuan Mao; Xinyan Wang; Can Rui; Lina Yan; Yiquan Wang; Chong Fan; Ping Li; Xin Zeng (Mycopathologia, 2020)

Tracking fluid sources for skarn formation using scapolite geochemistry: an example from the Jinshandian iron skarn deposit, Eastern China - Li-Ping Zeng; Xin-Fu Zhao; Johannes Hammerli; Tian-Wei-Teng Fan; Carl Spandler (Mineralium Deposita, 2020)

The research trends of metal-organic frameworks in environmental science: a review based on bibliometric analysis - Juan Li; Liangjie Wang; Yongqiang Liu; Yonghui Song; Ping Zeng; Yajie Zhang (Environmental Science and Pollution Research, 2020)

Effects of seasonal variation on soil microbial community structure and enzyme activity in a Masson pine forest in Southwest China - Song-ping Luo; Bing-hui He; Qing-ping Zeng; Nan-jie Li; Lei Yang (Journal of Mountain Science, 2020)

Detection of serum IgM and IgG for COVID-19 diagnosis - Ling Zhong; Junlan Chuan; Bo Gong; Ping Shuai; Yu Zhou; Yi Zhang; Zhilin Jiang; Dingding Zhang; Xiaoqi Liu; Shi Ma; Yi Huang; He Lin; et al. (Science China Life Sciences, 2020)

A challenge in anaerobic digestion of swine wastewater: recalcitrance and enhanced-degradation of dietary fibres - Zhuo Zeng; Ping Zheng; Cheng Shi; Meng Zhang; Yiyu Li; Wudi Zhang; Shengdao Shan (Biodegradation, 2019)

Excess copper effects on growth, uptake of water and nutrients, carbohydrates, and PSII photochemistry revealed by OJIP transients in Citrus seedlings - Qiang Li; Huan-Huan Chen; Yi-Ping Qi; Xin Ye; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Environmental Science and Pollution Research, 2019)

Correction to: Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2019)

Improving the simulation of East Asian summer monsoon with mesoscale enhancement in an AGCM - Zhongxian Li; Ping He; Jieshun Zhu; Haishan Chen; Gang Zeng; Weitao Deng (Climate Dynamics, 2019)

Study on Stability of Goaf Pillars in Daqiao Phosphate Mine: Theoretical Calculation and Field Investigation - Feifei Wang; Ping Zou; Zhonghua Meng; Aibing Li; Zhengyu Liu; Wanjie Hu; Zeng Ma (Geotechnical and Geological Engineering, 2019)

Whole genome sequencing of a MAGIC population identified genomic loci and candidate genes for major fiber quality traits in upland cotton (Gossypium hirsutum L.) - Gregory N. Thyssen; Johnie N. Jenkins; Jack C. McCarty; Linghe Zeng; B. Todd Campbell; Christopher D. Delhom; Md. Sariful Islam; Ping Li; Don C. Jones; Brian D. Condon; David D. Fang (Theoretical and Applied Genetics, 2019)

Challenges in predicting and simulating summer rainfall in the eastern China - Ping Liang; Zeng-Zhen Hu; Yunyun Liu; Xing Yuan; Xiaofan Li; Xingwen Jiang (Climate Dynamics, 2019)

Transient dispersion of an initial point pollutant concentration in wetland flows - Ping Wang; Li Zeng; Wenxin Huai (Environmental Science and Pollution Research, 2018)

Ore genesis of the Wusihe carbonate-hosted Zn-Pb deposit in the Dadu River Valley district, Yangtze Block, SW China: evidence from ore geology, S-Pb isotopes, and sphalerite Rb-Sr dating - Suo-Fei Xiong; Yong-Jun Gong; Shao-Yong Jiang; Xiao-Jing Zhang; Qian Li; Guo-Ping Zeng (Mineralium Deposita, 2018)

The importance of accounting for imperfect detection when estimating functional and phylogenetic community structure - Xingfeng Si; Marc W. Cadotte; Yuhao Zhao; Haonan Zhou; Di Zeng; Jiaqi Li; Tinghao Jin; Peng Ren; Yanping Wang; Ping Ding; Morgan W. Tingley (Ecology, 2018)
Incorporating imperfect detection when estimating species richness has become commonplace in the past decade. However, the question of how imperfect detection of species affects estimates of functional and phylogenetic community structure remains untested. We used long‐term counts of breeding bird species that were detected at least once on islands in a land‐bridge island system, and employed multi‐species occupancy models to assess the effects of imperfect detection of species on estimates of bird diversity and community structure by incorporating species traits and phylogenies. Our results showed that taxonomic, functional, and phylogenetic diversity were all underestimated significantly as a result of species’ imperfect detection, with taxonomic diversity showing the greatest bias. The functional and phylogenetic structure calculated from observed communities were both more clustered than those from the detection‐corrected communities due to missed distinct species. The discrepancy between observed and estimated diversity differed according to the measure of biodiversity employed. Our study demonstrates the importance of accounting for species’ imperfect detection in biodiversity studies, especially for functional and phylogenetic community ecology, and when attempting to infer community assembly processes. With datasets that allow for detection‐corrected community structure, we can better estimate diversity and infer the underlying mechanisms that structure community assembly, and thus make reliable management decisions for the conservation of biodiversity.

BDNF/TrkB Pathway Mediates the Antidepressant-Like Role of H2S in CUMS-Exposed Rats by Inhibition of Hippocampal ER Stress - Le Wei; Li-Yuan Kan; Hai-Ying Zeng; Yi-Yun Tang; Hong-Lin Huang; Ming Xie; Wei Zou; Chun-Yan Wang; Ping Zhang; Xiao-Qing Tang (NeuroMolecular Medicine, 2018)

Epidemiology and clinical characteristics of human coronaviruses OC43, 229E, NL63, and HKU1: a study of hospitalized children with acute respiratory tract infection in Guangzhou, China - Zhi-Qi Zeng; De-Hui Chen; Wei-Ping Tan; Shu-Yan Qiu; Duo Xu; Huan-Xi Liang; Mei-Xin Chen; Xiao Li; Zheng-Shi Lin; Wen-Kuan Liu; Rong Zhou (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

A new arbutin derivative from the leaves of Vaccinium dunalianum wight - Na Li; Wei-Lin Zeng; Xu-Lu Luo; Chong-Ren Yang; Ying-Jun Zhang; Yong Ding; Ping Zhao (Natural Product Research, 2018)

Xylastriasan A, a new cytochalasan from the fungus Xylaria striata - Chuan-Wen Lei; Zhi-Qin Yang; Yan-Ping Zeng; Yun Zhou; Yi Huang; Xin-Sheng He; Guo-You Li; Xiao-Hong Yuan (Natural Product Research, 2018)

Phenolic constituents from Rheum nobile and their antioxidant activity - Ye Fei; Juan Wang; Bing Peng; Jiangnan Peng; Jing-Hong Hu; Zu-Ping Zeng; Jing Chen; Qi-En Li; Zeng-Ping Gao; Xing-Li Yan (Natural Product Research, 2017)

Cross-neutralization of SARS coronavirus-specific antibodies against bat SARS-like coronaviruses - Lei-Ping Zeng; Xing-Yi Ge; Cheng Peng; Wanbo Tai; Shibo Jiang; Lanying Du; Zheng-Li Shi (Science China Life Sciences, 2017)

Saikosaponin D relieves unpredictable chronic mild stress induced depressive-like behavior in rats: involvement of HPA axis and hippocampal neurogenesis - Hong-Yan Li; Ying-Hua Zhao; Min-Jie Zeng; Fang Fang; Min Li; Ting-Ting Qin; Lu-Yu Ye; Hong-Wei Li; Rong Qu; Shi-Ping Ma (Psychopharmacology, 2017)

Elevated expression of CST1 promotes breast cancer progression and predicts a poor prognosis - Da-nian Dai; Yan Li; Bo Chen; Yong Du; Shi-bing Li; Shi-xun Lu; Zhi-ping Zhao; Ai-jun Zhou; Ning Xue; Tian-liang Xia; Mu-sheng Zeng; Qian Zhong; et al. (Journal of Molecular Medicine, 2017)
Cystatin SN (CST1) belongs to the type 2 cystatin (CST) superfamily, which restricts the proteolytic activities of cysteine proteases. CST1 has been recently considered to be involved in the development of several human cancers. However, the prognostic significance and function of CST1 in breast cancer remains unknown. In the current study, we found that CST1 was generally upregulated in breast cancer at both mRNA and protein level. Furthermore, overall survival (OS) and disease-free survival (DFS) in the low CST1 expression subgroup were significantly superior to the high CST1 expression subgroup (OS, p < 0.001; DFS, p < 0.001), which indicated that CST1 expression level was closely correlated to the survival risk of these patients. Univariate and multivariate analyses demonstrated that CST1 expression was an independent prognostic factor, the same as ER status and nodal status. Next, CST1 overexpression promoted breast cancer cell proliferation, clonogenicity, migration, and invasion abilities. By contrast, knockdown of CST1 attenuated these malignant characteristics in breast cancer cells. Collectively, our study indicates that CST1 cannot only serve as a significant prognostic indicator but also as a potential therapeutic target for breast cancer. Key messages High CST1 expression is negatively correlated with survival of breast cancer patients. CST1 promotes cell proliferation, clone formation, and metastasis in breast cancer cells. CST1 is a novel potential prognostic biomarker and therapeutic target for breast cancer.

Two ultraviolet radiation datasets that cover China - Hui Liu; Bo Hu; Yuesi Wang; Guangren Liu; Liqin Tang; Dongsheng Ji; Yongfei Bai; Weikai Bao; Xin Chen; Yunming Chen; Weixin Ding; Xiaozeng Han; et al. (Advances in Atmospheric Sciences, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Genetic characterization of H9N2 avian influenza virus in plateau pikas in the Qinghai Lake region of China - Yan Yan; Jin-Yan Gu; Zhuang-Chuan Yuan; Xin-Yu Chen; Zeng-Kui Li; Jing Lei; Bo-li Hu; Li-Ping Yan; Gang Xing; Min Liao; Ji-Yong Zhou (Archives of Virology, 2017)

NLRP3 is Required for Complement-Mediated Caspase-1 and IL-1beta Activation in ICH - Sheng-Tao Yao; Fang Cao; Jia-Lin Chen; Wei Chen; Rui-Ming Fan; Gang Li; You-Chao Zeng; Song Jiao; Xiang-Ping Xia; Chong Han; Qi-Shan Ran (Journal of Molecular Neuroscience, 2017)

Source analysis of organic matter in swine wastewater after anaerobic digestion with EEM-PARAFAC - Zhuo Zeng; Ping Zheng; Aqiang Ding; Meng Zhang; Ghulam Abbas; Wei Li (Environmental Science and Pollution Research, 2017)

Improvement of anti-nutritional effect resulting from β-glucanase specific expression in the parotid gland of transgenic pigs - Li-zeng Guan; Jin-shun Cai; Shuai Zhao; Yu-ping Sun; Jing-lan Wang; Yong Jiang; Gang Shu; Qing-yan Jiang; Zhen-fang Wu; Qian-yun Xi; Yong-liang Zhang (Transgenic Research, 2017)

Prolonged exposure to low-dose microcystin induces nonalcoholic steatohepatitis in mice: a systems toxicology study - Jun He; Guangyu Li; Jun Chen; Juan Lin; Cheng Zeng; Jing Chen; Junliang Deng; Ping Xie (Archives of Toxicology, 2017)

The unique origin of orange carrot cultivars in China - Zhen-Guo Ma; Xiao-Ping Kong; Li-Jie Liu; Cheng-Gang Ou; Ting-Ting Sun; Zhi-Wei Zhao; Zeng-Jian Miao; Jun Rong; Fei-Yun Zhuang (Euphytica, 2016)

Clitocine potentiates TRAIL-mediated apoptosis in human colon cancer cells by promoting Mcl-1 degradation - Jian-guo Sun; Feng Ruan; Xue-li Zeng; Jun Xiang; Xia Li; Ping Wu; Kwok Pui Fung; Fei-yan Liu (Apoptosis, 2016)

Protective Effects of Chinese Herbal Medicine Rhizoma drynariae in Rats After Traumatic Brain Injury and Identification of Active Compound - Wenzhu Wang; Haigang Li; Jintao Yu; Michael Hong; Jing Zhou; Lin Zhu; Yang Wang; Min Luo; Zian Xia; Zeng-Jin Yang; Tao Tang; Ping Ren; et al. (Molecular Neurobiology, 2016)

Mapping by sequencing in cotton (Gossypium hirsutum) line MD52ne identified candidate genes for fiber strength and its related quality attributes - Md. S. Islam; Linghe Zeng; Gregory N. Thyssen; Christopher D. Delhom; Hee Jin Kim; Ping Li; David D. Fang (Theoretical and Applied Genetics, 2016)

High expression of growth factor receptor-bound protein 14 predicts poor prognosis for colorectal cancer patients - Ping Yang; Jianchang Wei; Wanglin Li; Feng He; Shanqi Zeng; Tong Zhang; Zheng Sun; Jie Cao (Biotechnology Letters, 2016)

Imbalanced expression of Bcl-xL and Bax in platelets treated with plasma from immune thrombocytopenia - Jianlin Qiao; Yun Liu; Depeng Li; Yulu Wu; Xiaoqian Li; Yao Yao; Mingshan Niu; Chunling Fu; Hongchun Li; Ping Ma; Zhenyu Li; Kailin Xu; et al. (Immunologic Research, 2016)

Interaction of TIM4 and TIM3 induces T helper 1 cell apoptosis - Rong-Ti Ge; Lu Zeng; Li-Hua Mo; Ling-Zhi Xu; Huan-Ping Zhang; Hai-Qiong Yu; Min Zhang; Zhi-Gang Liu; Zhan-Ju Liu; Ping-Chang Yang (Immunologic Research, 2016)

Elevated expression of NLRP3 in patients with immune thrombocytopenia - Jianlin Qiao; Yun Liu; Xiaoqian Li; Yuan Xia; Yulu Wu; Depeng Li; Hongchun Li; Ping Ma; Feng Zhu; Zhenyu Li; Kailin Xu; Lingyu Zeng (Immunologic Research, 2016)

Erratum to: Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2016)

Bioaccessibility of heavy metals in vegetables and its association with the physicochemical characteristics - Weijian Pan; Yuan Kang; Ning Li; Lixuan Zeng; Qiuyun Zhang; Jin Wu; Ping Lu; Jiwen Luo; Xinmei Guo (Environmental Science and Pollution Research, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

The application study on the multi-scales integrated prediction method to fractured reservoir description - Shuang-Quan Chen; Lian-Bo Zeng; Ping Huang; Shao-Han Sun; Wan-Lu Zhang; Xiang-Yang Li (Applied Geophysics, 2016)

Global patterns and climate drivers of water‐use efficiency in terrestrial ecosystems deduced from satellite‐based datasets and carbon cycle models - Yan Sun; Shilong Piao; Mengtian Huang; Philippe Ciais; Zhenzhong Zeng; Lei Cheng; Xiran Li; Xinping Zhang; Jiafu Mao; Shushi Peng; Benjamin Poulter; Xiaoying Shi; et al. (Global Ecology and Biogeography, 2016)
Aim To investigate how ecosystem water‐use efficiency ( WUE ) varies spatially under different climate conditions, and how spatial variations in WUE differ from those of transpiration‐based water‐use efficiency ( WUE t ) and transpiration‐based inherent water‐use efficiency ( IWUE t ). Location Global terrestrial ecosystems. Methods We investigated spatial patterns of WUE using two datasets of gross primary productivity ( GPP ) and evapotranspiration ( ET ) and four biosphere model estimates of GPP and ET . Spatial relationships between WUE and climate variables were further explored through regression analyses. Results Global WUE estimated by two satellite‐based datasets is 1.9 ± 0.1 and 1.8 ± 0.6 g C m −2 mm −1 lower than the simulations from four process‐based models (2.0 ± 0.3 g C m −2 mm −1 ) but comparable within the uncertainty of both approaches. In both satellite‐based datasets and process models, precipitation is more strongly associated with spatial gradients of WUE for temperate and tropical regions, but temperature dominates north of 50° N . WUE also increases with increasing solar radiation at high latitudes. The values of WUE from datasets and process‐based models are systematically higher in wet regions (with higher GPP ) than in dry regions. WUE t shows a lower precipitation sensitivity than WUE , which is contrary to leaf‐ and plant‐level observations. IWUE t , the product of WUE t and water vapour deficit, is found to be rather conservative with spatially increasing precipitation, in agreement with leaf‐ and plant‐level measurements. Main conclusions WUE , WUE t and IWUE t produce different spatial relationships with climate variables. In dry ecosystems, water losses from evaporation from bare soil, uncorrelated with productivity, tend to make WUE lower than in wetter regions. Yet canopy conductance is intrinsically efficient in those ecosystems and maintains a higher IWUE t . This suggests that the responses of each component flux of evapotranspiration should be analysed separately when investigating regional gradients in WUE , its temporal variability and its trends.

Source Apportionment Coupled with Gas/Particle Partitioning Theory and Risk Assessment of Polycyclic Aromatic Hydrocarbons Associated with Size-Segregated Airborne Particulate Matter - Yunbo Zhai; Ping Li; Yun Zhu; Bibo Xu; Chuan Peng; Tengfei Wang; Caiting Li; Guangming Zeng (Water, Air, & Soil Pollution, 2016)

Combination of Estrogen and Immunosuppressive Agents to Establish a Mouse Model of Candidiasis with Concurrent Oral and Vaginal Mucosal Infection - Le Wang; Chong Wang; Huan Mei; Yongnian Shen; Guixia Lv; Rong Zeng; Ping Zhan; Dongmei Li; Weida Liu (Mycopathologia, 2016)

Quantitatively evaluating detoxification of the hepatotoxic microcystin-LR through the glutathione (GSH) pathway in SD rats - Xiaochun Guo; Liang Chen; Jun Chen; Ping Xie; Shangchun Li; Jun He; Wei Li; Huihui Fan; Dezhao Yu; Cheng Zeng (Environmental Science and Pollution Research, 2015)

Isolation of a new flavanone from Daidai fruit and hypolipidemic activity of total flavonoids extracts - Ling-Jun Zeng; Dan Chen; Qing-De Huang; Qun Huang; Yun-Fang Lian; Wei-Wei Cai; Hua-Ping Zeng; Yi-Li Lin (Natural Product Research, 2015)

The aflatoxin-detoxifizyme specific expression in mouse parotid gland - Li-zeng Guan; Yu-ping Sun; Jin-shun Cai; Han-dong Wu; Long-zheng Yu; Yong-liang Zhang; Qian-yun Xi (Transgenic Research, 2015)

Effects of l-tryptophan-supplemented dietary on growth performance and 5-HT and GABA levels in juvenile Litopenaeus vannamei - Yu-Ping Sun; Li-Zeng Guan; Jie-Hua Xiong; Qian-Yun Xi; Yong-Liang Zhang (Aquaculture International, 2015)

Determination of multiple elements in samples of the medicinal plant Marsdenia tenacissima and estimation of geographic origin via pattern recognition techniques - Chao Li; Qiao-sheng Guo; Sheng-chao Yang; Kai-yan Zheng; Wang-ping Li; Zhen-gui Meng; Xiang-zeng Xu (Journal of Natural Medicines, 2015)

Contamination of commercially available seafood by key diarrhetic shellfish poisons along the coast of China - Chao Lin; Zeng-Shan Liu; Cai-Yun Tan; Yi-Ping Guo; Lin Li; Hong-Lin Ren; Yan-Song Li; Pan Hu; Sheng Gong; Yu Zhou; Shi-Ying Lu (Environmental Science and Pollution Research, 2015)

Isolation and characterization of polymorphic microsatellites in the perennial herb Euphorbia kansui using paired-end Illumina shotgun sequencing - Xiao-Hao Yan; Min-Feng Fang; Zeng-Qiang Qian; Zhan-Lin Liu; Ma-Li Wang; Cai-Ping Tian; Meng-Han Du; Yin-Jun Li; Zhong-Hu Li; Gui-Fang Zhao (Conservation Genetics Resources, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Lipid response to short-term chilling shock and long-term chill hardening in Jatropha curcas L. seedlings - Zhong-Guang Li; Hua-Zong Zeng; Ping-xing Ao; Ming Gong (Acta Physiologiae Plantarum, 2014)

Reservoir Flood Routing Considering the Non-Stationarity of Flood Series in North China - Hang Zeng; Ping Feng; Xin Li (Water Resources Management, 2014)

Differential role of Rac in the basolateral amygdala and cornu ammonis 1 in the reconsolidation of auditory and contextual Pavlovian fear memory in rats - Ping Wu; Zeng-Bo Ding; Shi-Qiu Meng; Hao-Wei Shen; Shi-Chao Sun; Yi-Xiao Luo; Jian-Feng Liu; Lin Lu; Wei-Li Zhu; Jie Shi (Psychopharmacology, 2014)

The Application of Laser Microdissection in Molecular Detection and Identification of Aspergillus fumigatus from Murine Model of Acute Invasive Pulmonary Aspergillosis - Chong Wang; Ping Zhan; Le Wang; Rong Zeng; Yongnian Shen; Guixia Lv; Dongmei Li; Shuwen Deng; Weida Liu (Mycopathologia, 2014)

Enhancement of nitrogen and phosphorus removal from eutrophic water by economic plant annual ryegrass (Lolium multiflorum) with ion implantation - Miao Li; Guo-ping Sheng; Yue-jin Wu; Zeng-liang Yu; Gary S. Bañuelos; Han-qing Yu (Environmental Science and Pollution Research, 2014)

Concentrations, Sources, and Risk Assessment of Polychlorinated Biphenyls in Vegetables Near a Waste-Incinerator Site, South China - Lixuan Zeng; Ning Li; Dingding Shao; Yuan Kang; Qiuyun Zhang; Ping Lu; Laisheng Li; Jiwen Luo; Xingmei Guo (Archives of Environmental Contamination and Toxicology, 2014)

Positive matrix factorization as source apportionment of soil lead and cadmium around a battery plant (Changxing County, China) - Jian-long Xue; Yu-you Zhi; Li-ping Yang; Jia-chun Shi; Ling-zao Zeng; Lao-sheng Wu (Environmental Science and Pollution Research, 2014)

Over-expression of heat shock factor gene (AtHsfA1d) from Arabidopsis thaliana confers formaldehyde tolerance in tobacco - Hong-Juan Nian; Dao-Jun Zhang; Zhi-Dong Zeng; Jin-Ping Yan; Kun-Zhi Li; Li-Mei Chen (Acta Physiologiae Plantarum, 2014)

A dwarfing mutant caused by deactivation function of alpha subunit of the heterotrimeric G-protein in rice - De-wei Yang; Xiang-hua Zheng; Chao-ping Cheng; Wen-da Wang; Deng-hui Xing; Li-bin Lu; Chen-de Liu; Ning Ye; Mei-juan Zeng; Xin-fu Ye (Euphytica, 2014)

Clitocine targets Mcl-1 to induce drug-resistant human cancer cell apoptosis in vitro and tumor growth inhibition in vivo - Jian-guo Sun; Hua Li; Xia Li; Xueli Zeng; Ping Wu; Kwok-Pui Fung; Fei-yan Liu (Apoptosis, 2014)

Stripe rust resistance and genes in Chinese wheat cultivars and breeding lines - Qing-Dong Zeng; De-Jun Han; Qi-Lin Wang; Feng-Ping Yuan; Jian-Hui Wu; Li Zhang; Xiao-Jie Wang; Li-Li Huang; Xian-Ming Chen; Zhen-Sheng Kang (Euphytica, 2014)
Stripe rust, caused by Puccinia striiformis f. sp. tritici ( Pst ), is one of the most important diseases on wheat in China. To assess resistance in wheat cultivars and breeding lines in China, 330 leading cultivars and 164 advanced breeding lines were evaluated with stripe rust. In the greenhouse tests, seedlings of the entries were inoculated separately with several Pst pathotypes. In the field tests, the entries were evaluated for stripe rust resistance in Yangling, Shaanxi Province artificially inoculated and in Tianshui, Gansu Province under natural infection of Pst . The oversummering/wintering and spring epidemic zones of resistance genes were postulated using molecular markers for Yr5 , Yr9 , Yr10 , Yr15 , Yr17 , Yr18 , and Yr26 , in combination with resistance spectra. Out of the 494 wheat entries, 16 (3.24 %) entries had all-stage resistance (ASR) in all race tests, 99 (20.04 %) had adult-plant resistance (APR), 28 (5.67 %) were considered to have slow-rusting (SR), and 351 (71.05 %) were susceptible to one or more races in both seedling and adult-plant stages. Advanced breeding lines had a higher percentage (37.2 %) of resistant entries (The sum of ASR, APR and SR) than leading cultivars (24.85 %). Among the epidemic regions, southern Gansu had a higher percentage of resistant entries than any other regions. Based on stripe rust reactions and molecular markers, two cultivars were found to possibly have Yr5 while no entries have Yr10 or Yr15 . Resistance genes Yr9 , Yr17 , Yr18 , and Yr26 were found in 134 (29.4 %), 45 (9.1 %), 10 (2 %), and 15 (3 %) entries, respectively.

Transport of a volatile contaminant in a free-surface wetland flow - Jue Yuan; Li Zeng; Yijun Zhao; Yihong Wu; Ping Ji; Bin Chen (Frontiers of Earth Science, 2014)

Chromium level and intake from Chinese made tea - Wei-hao Li; Hai-ping Zhou; Ning Li; Sai-di Wang; Xiao-juan Liu; Zeng-jun Jin; Yan-zhen Bu; Zhi-xue Liu (Food Additives & Contaminants Part B-Surveillance, 2013)

Sorption of ammonium and phosphate from aqueous solution by biochar derived from phytoremediation plants - Zheng Zeng; Song-da Zhang; Ting-qiang Li; Feng-liang Zhao; Zhen-li He; He-ping Zhao; Xiao-e Yang; Hai-long Wang; Jing Zhao; Muhammad Tariq Rafiq (Journal of Zhejiang University-SCIENCE B, 2013)

Musca Domestica Larva Lectin Induces Apoptosis in BEL-7402 Cells Through a Ca2+/JNK-mediated Mitochondrial Pathway - Chun-Ling Wang; Yan Xia; Jian-Zeng Nie; Minghui Zhou; Rong-Ping Zhang; Li-Li Niu; Li-Hua Hou; Xiao-Hong Cao (Cell Biochemistry and Biophysics, 2013)

Dietary consumption and diet diversity and risk of developing bladder cancer: results from the South and East China case–control study - Fatima Isa; Li-Ping Xie; Zhiquan Hu; Zhaohui Zhong; Marjolein Hemelt; Raoul C. Reulen; Y. C. Wong; Po-Chor Tam; Kai Yang; Chao Chai; Xing Zeng; Yilan Deng; et al. (Cancer Causes & Control, 2013)

Arbuscular mycorrhizal symbiosis and active ingredients of medicinal plants: current research status and prospectives - Yan Zeng; Lan-Ping Guo; Bao-Dong Chen; Zhi-Peng Hao; Ji-Yong Wang; Lu-Qi Huang; Guang Yang; Xiu-Ming Cui; Li Yang; Zhao-Xiang Wu; Mei-Lan Chen; Yan Zhang (Mycorrhiza, 2013)

Crystal structure and activating effect on RyRs of AhV_TL-I, a glycosylated thrombin-like enzyme from Agkistrodon halys snake venom - Fuxing Zeng; Bing Shen; Zhongliang Zhu; Ping Zhang; Yonghua Ji; Liwen Niu; Xu Li; Maikun Teng (Archives of Toxicology, 2013)

An Arabidopsis mutant atcsr-2 exhibits high cadmium stress sensitivity involved in the restriction of H2S emission - Ya-wei Li; Ze-hua Gong; Yao Mu; Yi-xian Zhang; Zeng-jie Qiao; Li-ping Zhang; Zhu-ping Jin; Hua Li; Yan-xi Pei (Journal of Zhejiang University-SCIENCE B, 2012)

Abundance and composition of ammonia-oxidizing bacteria and archaea in different types of soil in the Yangtze River estuary - Xiao-ran Li; Yi-ping Xiao; Wen-wei Ren; Zeng-fu Liu; Jin-huan Shi; Zhe-xue Quan (Journal of Zhejiang University-SCIENCE B, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

China’s wastewater discharge standards in urbanization - Wen-Wei Li; Guo-Ping Sheng; Raymond J. Zeng; Xian-Wei Liu; Han-Qing Yu (Environmental Science and Pollution Research, 2012)

Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Characterization of the expression profiles of calpastatin (CAST) gene in chicken - Zeng-Rong Zhang; Xiao-Song Jiang; Hua-Rui Du; Qing Zhu; Xiao-Cheng Li; Chao-Wu Yang; Yi-Ping Liu (Molecular Biology Reports, 2012)

Erratum to: Autophagy precedes apoptosis during the remodeling of silkworm larval midgut - Eleonora Franzetti; Zhi-Jun Huang; Yan-Xia Shi; Kun Xie; Xiao-Juan Deng; Jian-Ping Li; Qing-Rong Li; Wan-Ying Yang; Wen-Nian Zeng; Morena Casartelli; Hui-Min Deng; Silvia Cappellozza; et al. (Apoptosis, 2012)

Microsporogenesis, microgametogenesis, and pollen morphology of Ambrosia artemisiifolia L. in China - Jia-Xi Liu; Min Wang; Bing-Xiao Chen; Ping Jin; Jing-Yu Li; Ke Zeng (Plant Systematics and Evolution, 2012)

Clinical characteristics of critical patients with pandemic influenza A (H1N1) virus infection in Chengdu, China - Li-hui Deng; Yi-lan Zeng; Ping Feng; Ya-ling Liu; Li-chun Wang; Yun Bai; Hong Tang (Journal of Zhejiang University-SCIENCE B, 2012)

Minimally-invasive treatment of communicating hydrocephalus using a percutaneous lumboperitoneal shunt - Lu Jia; Zhong-xin Zhao; Chao You; Jia-gang Liu; Si-qing Huang; Min He; Pei-gang Ji; Jie Duan; Yi-jun Zeng; Guo-ping Li (Journal of Zhejiang University-SCIENCE B, 2011)

Molecular cytogenetic identification of a new wheat-Thinopyrum substitution line with stripe rust resistance - Li-Jun Hu; Guang-Rong Li; Zi-Xian Zeng; Zhi-Jian Chang; Cheng Liu; Jian-Ping Zhou; Zu-Jun Yang (Euphytica, 2011)

Soil microbial properties under N and P additions in a semi-arid, sandy grassland - Lu-Jun Li; De-Hui Zeng; Zhan-Yuan Yu; Zhi-Ping Fan; Rong Mao (Biology and Fertility of Soils, 2010)

Sensitive Phosphorimetric Determination of Bumetanide in Human Urine with Its Inhibition Effect on the Formation of [Fe-morin] 3+ Complex - Li-Qing Zeng; Jia-Ming Liu; Fei-Ming Li; Xiao-Mei Huang; Li-Ping Lin; Xin-Xing Wang; Li-Hong Zhang; Chang-Qing Lin (Journal of Fluorescence, 2010)

The efficacy of FMD vaccine reduced non-structural proteins with a mAb against 3B protein - Dong Li; Zai-Xin Liu; Pu Sun; Yong-Liang Li; Zeng-Jun Lu; Mei-Na Tian; Ying-Li Chen; Bao-Xia Xie; Hui-Fang Bao; Yuan-Fang Fu; Yi-Mei Cao; Ping-Hua Li; et al. (Veterinary Research Communications, 2010)

Meiotic nondisjunction in resynthesized Brassica napus and generation of aneuploids through microspore culture and their characterization - Jing Wen; Xin-hua Zeng; Yuan-yuan Pu; Li-ping Qi; Zai-yun Li; Jin-xing Tu; Chao-zhi Ma; Jin-xiong Shen; Ting-dong Fu (Euphytica, 2010)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Quantification of Three Key Enzymes Involved in Artemisinin Biogenesis in Artemisia annua by Polyclonal Antisera-Based ELISA - Qing-Ping Zeng; Xiao-Mei Zeng; Lu-Lu Yin; Rui-Yi Yang; Li-Ling Feng; Xue-Qin Yang (Plant Molecular Biology Reporter, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Prediction of hidden Au and Cu–Ni ores from depleted mines in Northwestern China: four case studies of integrated geological and geophysical investigations - Ping Shen; Yuanchao Shen; Tiebing Liu; Guangming Li; Qingdong Zeng (Mineralium Deposita, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Expression and characteristic of synthetic human epidermal growth factor (hEGF) in transgenic tobacco plants - Jie-Ying Bai; Lin Zeng; Yuan-Lei Hu; Yan-Fang Li; Zhong-Ping Lin; Shi-Chen Shang; Yan-Sheng Shi (Biotechnology Letters, 2007)

Genes expression analyses of sea-island cotton (Gossypium barbadense L.) during fiber development - Li-Li Tu; Xian-Long Zhang; Shao-Guang Liang; Di-Qiu Liu; Long-Fu Zhu; Fan-Chang Zeng; Yi-Chun Nie; Xiao-Ping Guo; Feng-Lin Deng; Jia-Fu Tan; Li Xu (Plant Cell Reports, 2007)

Tegaserod for dyspepsia and reflux symptoms in patients with chronic constipation: an exploratory open-label study - Juan Zeng; Xiu-Li Zuo; Yan-Qing Li; Wei Wei; Guo-Ping Lv (European Journal of Clinical Pharmacology, 2007)

Determination of Trace Mercury by Solid Substrate-Room Temperature Phosphorimetry Quenching Method Based on Catalytic Effect of Hg2+on Formation of the Ion Association Complex [Sn(XO)6]4+·[(Fin)4] - Jia-Ming Liu; Ruo-Hong Wu; De-Chang Li; Ping Zhou; Min-Min Zheng; Xiao-Yi Zeng; Dong-Xia Liu; Xiao-Mei Huang; Guo-Hui Zhu (Journal of Fluorescence, 2006)

Spatial changes of wind erosion-caused landscapes and their relation with wind field in China - Zhang Guo-ping; Liu Ji-yuan; Zhang Zeng-xiang; Zhao Xiao-li; Zhou Quan-bin (Journal of Geographical Sciences, 2002)